Tsenguluso nga ha thuthuwedzo i bveledzwaho nga kushumiselwe kwa thekhinolodzhi kha Tshivenda - Makumbane, Livhuwani Meriam (My University, 2014)
Refer to the document
Thesis (M.A. (African Languages)) --University of Limpopo, 2014
Keywords: Technology on language; Venda language; Communication; Communication and technology; Venda language -- Technical Venda